Kepemimpinan Kepala Sekolah Dalam Membangun School Branding Berbasis Pendidikan Karakter di Sdn Kotakulon 2 Bondowoso - Marnita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The increasingly intense competition among elementary schools requires them to build a distinctive identity that differentiates them from other institutions. This study aims to describe the implementation of character-based school branding and to analyze the principal's strategies in building it at SDN Kotakulon 2 Bondowoso. This study used a qualitative approach with a phenomenological method. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model (data condensation, data display, and conclusion drawing), with data validity tested through source and technique triangulation. The results indicate that the principal implemented school branding through the “BERSERI Program”, targeting four core character values: religiosity, discipline, friendliness/communicativeness, and environmental care, with varying degrees of internalization across values. The strategies applied comprise five complementary aspects: brand positioning, brand identity, brand personality, digital branding, and stakeholder collaboration, carried out through a participatory cycle from parent-needs surveys to routine biweekly evaluation. This study concludes that consistent principal leadership in embedding character values across all operational aspects of the school is key to successful school branding at public elementary schools, offering a replicable model for other public elementary schools with limited resources.
Finalisasi oleh Agus 21 Juli 2026